Keeping cell identity in arabidopsis requires PRC1 RING-finger homologs that catalyze H2A monoubiquitination - Bratzel, Fabian; Koch, Marcus; Calonje, Myriam (Current biology, 2010)
Summary: Polycomb group (PcG) proteins form conserved regulatory complexes that modify chromatin to repress the genes that are not required in a specific differentiation status [1]. In animals, the two best-characterized PcG complexes are PRC2 and PRC1, which respectively possess histone 3 lysine 27 (H3K27) trimethyltransferase [2-4] and histone 2A lysine 119 (H2AK119) E3 ubiquitin ligase activities [5-7]. In Arabidopsis, PRC2 activity is also required for the gene silencing mechanism [8]; however, the existence of PRC1 has been questioned, because plant genomes do not encode clear PRC1 components and H2A monoubiquitination has not been detected [6, 9]. Conversely, recent reports have unveiled the presence of homologs to PRC1 components that together with plant-specific proteins could be part of the long-sought PRC1-like complexes [10, 11]. Here we show that the PRC1 RING-finger homologs AtBMI1A and AtBMI1B are implicated in the repression of embryonic and stem cell regulators. Plants impaired in AtBMI1A and AtBMI1B show derepression of embryonic traits in somatic cells, displaying a phenotype similar to plants mutant in PRC2 components [12-14]. Our data demonstrate that the AtBMI1A/B proteins mediate H2A monoubiquitination in Arabidopsis and that this mark, together with PRC2-mediated H3K27 trimethylation, plays a key role in maintaining cell identity.